Urinary tract infection among primigravid singleton pregnancies: a retrospective study from the North of Jordan - Hatamleh, Reem; Al-Akour, Nemeh; Al-Bakheet, Wafa'a; Atout, Maha; El-Banna, Majeda (Frontiers in Global Women's Health, 2025)
ObjectivesUrinary tract infections (UTIs) are common during pregnancy and can lead to adverse maternal and neonatal outcomes. Despite their significance, data on UTI prevalence and associated factors among pregnant women in Jordan remain limited. This study aimed to determine the prevalence of UTI and its associated factors among pregnant women in the northern Jordan.MethodsWe conducted a retrospective study using a convenience sampling method to review the records of pregnant women registered in the King Abdullah University Hospital database between January 2017 and January 2020.ResultsThe study found that the prevalence of urinary tract infection (UTI) was 8.9%. Positive predictors included an interaction between chronological age and level of education (OR = 1.139; 95% CI: 1.040–1.248; p = 0.01), being in the third trimester of pregnancy (OR = 1.856; 95% CI: 1.052–3.273; p = 0.03), prolonged hospitalization (OR = 6.784; 95% CI: 4.075–11.292; p < 0.001), and anemia (OR = 3.662; 95% CI: 2.185–6.138; p < 0.001). Negative predictors included having a university degree (OR = 0.027; 95% CI: 0.002–0.344; p = 0.01) and being at the younger or older age during pregnancy (OR = 0.904; 95% CI: 0.839–0.974; p = 0.01).ConclusionThe study concluded that the prevalence of UTI among singleton primigravida pregnant women was high, given the potential consequences of infection during pregnancy. Therefore, appropriate interventional measures should be implemented by the government and relevant stakeholders to reduce the prevalence of the infection and its associated complications.